In vitro large-scale propagation and genetic fidelity of Toona sinensis (Juss.)M. Roem., an economically important vegetable tree - Hou, J.; Wang, D.; Su, P.; Ding, S.; Wu, L.
Toona sinensis (Juss.)M.Roem., is an economically important seasonable vegetable tree with a wide range of nutritional, medicinal, and industrial values. The existing breeding methods can no longer sustainably meet the growing and annual production demands for T. sinensis buds. An efficient and cost-effective in vitro large-scale micropropagation procedure for T. sinensis was developed from shoot stems with axillary or terminal buds through the processes of callus elimination, multiple shoot induction and hydroponic acclimation of the regenerated plantlets. Plant growth regulators, explant type, explant age and activated charcoal (AC)play an important role in multiple shoot induction and callus reduction. The highest shoot induction frequency (97.8 percent)with a mean number of shoots equal to 7.6 and a relatively smaller callus (0.3 cm in diameter)was obtained from the in vitro culture of 75-day-old shoot stems with axillary buds in Murashige and Skoog (MS)medium augmented with 1.0 mg l?p1 (BN6-benzyladenine (6-BA)and 0.2 mg l?p1 (Bindole-3-acetic acid (IAA). In addition, a complete plantlet with strong roots and mature leaves could be obtained directly by culturing the shoot stem segment on medium containing at least 0.5 g l?p1 (BAC, which reveals a new direction for the industrialized propagation of T. sinensis. Among the PGRs tested, a low concentration (0.5 mg l?p1(B)of zeatin (ZT)was found to be the most conducive to shoot elongation. We also found that low concentrations of auxin, activated carbon, sucrose and a low macronutrient strength are more beneficial for in vitro adventitious root formation. The highest rooting response (100 percent)with 5.7 roots produced per shoot was achieved in 1/4 MS medium with the addition of 0.5 mg l?p1 (Bpotassium salt of indole butyric acid (K-IBA), 0.5 g l?p1 (BAC, and 10.0 g l?p1 (Bsucrose. In addition, the major challenge of the low transplanting survival rate of regenerated T. sinensis plants was solved by adopting an ex-vitro hydroponic domestication strategy in a mini-incubator. The plants were successfully hardened in a transplanting mixture of garden soil, perlite, vermiculite and Pindstrup substrate (3:1:1:3), and the transplanting survival rate was 95.3 percent. Inter simple sequence repeat (ISSR)assessment revealed no difference between the regenerated plants and the mother plants. The micropropagation protocol established in this study will lay the foundation for germplasm conservation of T. sinensis and its sustainable utilization in food.s
Keywords: TOONA SINENSIS; MULTIPLE SHOOT INDUCTION; CALLUS REDUCTION; HYDROPONIC DOMESTICATION; GENETIC STABILITY ASSESSMENT